The novel ageing-induced long non-coding RNA MIRIAL controls endothelial cell and mitochondrial function. (14th October 2021) - Kohnle, C; Theodorou, K; Koziarek, S; Busscher, D; Sommer, J; Wagner, J U G; Wittig, I; Dimmeler, S; Boon, R A
Abstract:  : Vascular ageing is a key risk factor for cardiovascular diseases and is characterised by a continuous decline in endothelial function. Despite progress in recent years, the molecular mechanisms for this deterioration remain incompletely understood. Long non-coding RNAs (lncRNAs) are a heterogeneous class of RNAs that have been shown to regulate gene expression and protein function, however, little is known about their role in the ageing-associated dysregulation of endothelial cell (EC) function. In this study, we aimed to identify and functionally characterise a novel ageing-regulated lncRNA in ECs. Using RNA sequencing data of cardiac ECs from 12 weeks young and 20 months old mice, we identified Mirial as an ageing-induced lncRNA (1.32-fold, p=0.ehab724.33565). MIRIAL is conserved between mice and humans and has no obvious coding potential. GapmeR-mediated silencing of MIRIAL in human umbilical vein ECs (HUVECs) decreased cell proliferation by 50%, migration by 24% (p=0.045) and basal angiogenic sprouting by 53% (p=0.0029), while increasing VEGF-A-stimulated sprouting by 50% (p=0.0139) and not affecting apoptosis or senescence. Subcellular fractionation of HUVECs revealed that MIRIAL was predominantly associated with the chromatin (80%). Pathway analysis of RNA sequencing data showed an overrepresentation of upregulated p53 target genes upon MIRIAL knockdown in HUVECs which was validated using qRT-PCR (1.8–5.2-fold increased). Using siRNA against p53 we showed that this effect is fully dependent on the presence of p53. Moreover, p53 and its phosphorylated form (Ser15) were both increased (1.8-fold, p=0.01 and 2.9-fold, p=0.02) after MIRIAL silencing. Intriguingly, RNA immunoprecipitation revealed that MIRIAL physically interacts with p53 (3.75-fold enriched, p=0.0067). To further study the interactome of MIRIAL, we performed RNA pulldown assays followed by mass spectrometry analysis of bound proteins, which identified the ageing-associated prohibitin (PHB) 1 and 2 to potentially interact with MIRIAL. Similar to MIRIAL knockdown, siRNA-mediated PHB 1 or 2 silencing caused proliferative defects. Further, PHBs are known to physically interact with p53 and control mitochondrial metabolism, a key factor in cellular ageing. Interestingly, silencing of MIRIAL in HUVECs increased mitochondrial mass (1.8-fold, p=0.0008) and spare respiratory capacity (1.95-fold) with the latter being decreased in isolated aged murine ECs. Taken together, MIRIAL is an ageing-induced lncRNA in ECs acting as a key regulator of metabolic and cellular function. MIRIAL promotes cell proliferation, migration and basal angiogenic sprouting while decreasing mitochondrial function and VEGF-A-stimulated sprouting. We hypothesise that MIRIAL influences p53 signalling and mitochondrial respiration through PHB 1 and 2. The present study suggests that modulation of MIRIAL expression may be a promising strategy to prevent or even reverse ageing-induced functional decline of ECs. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): European Research Council (ERC) Starting Grant: Non-coding RNA in Vascular Ageing (NOVA)